The End of History in Kevin Barry’s City of Bohane (2011)? - Sylvie Mikowski (Angles)
This paper examines the issue of time and history in Kevin Barry’s 2011 novel City of Bohane, a mix of dystopia and satire in which post-Celtic Tiger, post-2008 “bust” Ireland is thinly disguised. That imaginary, dystopian world seems arrested in an eternal present, having reduced the historical past to the status of mere traces, the origin of which has been lost, while the future is jeopardized by entropy. However, the novel is not a critical dystopia in that the inhabitants of Bohane do not show any sign of protest or rebellion, numbed as they are by the pleasures of consumption of drugs or other material goods. The second part of the chapter analyses the different elements of the parody of contemporary Ireland and of the way neoliberalism has reduced the sacred cows of history—republicanism, nationalism, Catholicism—to devaluated signifiers. City of Bohane is comparable to visual artist Seán Hillen’s series of photomontage Irelantis, in which the incongruous, preposterous superimposition of a mythologized past with an equally artificial, implausible future is meant to set the onlooker aback, in the image of the sudden and unforeseeable transformation of an archaic, conservative, backward society into a globalized, multicultural vanguard of Western neo-liberalism.